PENGARUH SEMANGAT DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA KPD KOTA PALANGKA RAYA - Sunarmi, Sunarmi .; Pamungkur, Pamungkur . (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to determine and analyze the effect of work spirit and work motivation on employee performance at KPD kota Palangka Raya. The data used in the study are primary data by distributing questionnaires to 55 respondents of KPD kota Palangka Raya employees. This study uses multiple linear regression analysis techniques with the SPSS version 22 statistical application. Simultaneously, Work Spirit and Motivation affect employee performance, Partially, Work Spirit affects employee performance, Motivation affects employee performance. The R2 value is 0.629, meaning that around 62.9% of the Employee Performance variable is explained by the Work Spirit and Motivation variables, while the remaining 37.1% is explained by other factors that were not studied. The conclusion is that in order for work spirit and work motivation to remain optimal, the management tries to keep the store open, reduce employee working hours, only 20 days, and sell online.